The opioid epidemic and headache: Experience of a general neurology consult service. (8th December 2020) - Fearon, Conor; Moloney, Kevin; Chalissery, Albi; Ferguson, Damien; Redmond, Janice
Background: Headaches represent a significant proportion of referrals to any neurology consult service, of which many are migrainous. Regular use of opioids can lead to medication overuse headache in these patients and in some cases, dependence. The epidemic of opioid abuse represents a serious public health concern, with long term use of opioids associated with risk of misuse, abuse, addiction and even overdose. Methods: We audited headache referrals to the neurology consult service in an acute tertiary hospital over three 6-month periods between 2012 and 2019. Appropriateness of referrals with respect to NICE guidelines and initial treatments strategies were assessed. Results: The majority of headache disorders seen were migrainous and we found an alarming and repeated trend of early opioid prescribing in the initial acute setting (up to 56%). Conclusions: Further education of healthcare professionals and patients is urgently required to prevent this group becoming victims of the growing global opioid epidemic.